Airway Evaluation to Predict Difficult Laryngoscopy: Evaluation of Routine Parameters and Defining the Cutoff Value for Skin to Epiglottis Distance in Nepalese Population - Thapa, Ajay Singh; Yadav, Rajesh Kumar; Shah, Rakesh; Bhattarai, Anish (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Anesthesiologist is responsible for securing a continuously patent airway, failure to do so within critical minitues results in hypoxic consequences. It is essential to able to predict difficult laryngoscopy and intubation for which conventional airway examinations for relied upon. These conventional airway examinations have been found not to be hundred percent sensitive or specific and have found to have high inter observer variability. In such context and in the absence of adequate datas on Nepalese population, this study was conducted to aid to the data of airway examination parameters in Nepalese population and to find the place of ultrasonography in preanesthesia airway examination. Aim: To evaluate different preanesthesia airway examination parameters and to find the cutoff value of skin to epiglottis distance. Methods The study included all 120 cases posted for elective surgeries. All the patients underwent preanesthesia airway examination and the parameters were noted by one anesthesiologist. All the patients also underwent ultrasonography of airway and skin to epiglottis distance was measured and noted by another anesthesiologists. All the patients underwent surgery under general anesthesia after laryngoscopy and intubation. The observed parameters and skin to epiglottis distance were used for statistical analysis. Results Prevalence of difficult intubation was 9.4%. Conventional airway examination parameters were observed to be very less sensitive and have less positive predictive value but the specificity and negative predictive value were high. Thyromental distance was observed to have highest sensitivity of 65% and sternomental distance was observed to highest specificity of 96.5%. In difficult intubation group, the mean of skin to epiglottis distance was 16.57±0.97 mm and the calculated cutoff value was 14.63 mm. Conclusions Prevalence of Laryngoscopy difficult is high. he conventional airway examination tests are useful but may not be totally relied upon and ultrasonography can be a helpful aid.